Efficacy of positive psychotherapy in reducing negative and enhancing positive psychological outcomes: a meta-analysis of randomised controlled trials - Nexhmedin Morina; Thole Hilko Hoppen (BMJ Open)
Objective Positive psychotherapy (PPT) aims at increasing positive affect, meaning and engagement. We aimed to synthesise the available evidence on PPT efficacy.Design We conducted a preregistered systematic literature search and meta-analysis of randomised controlled trials examining the efficacy of PPT for increasing positive (eg, satisfaction with life) or decreasing negative psychological outcomes (eg, depression).Data sources Medline, PsycINFO and Web of Science from 2006 (ie, inception of PPT) to February 2020 as well as related systematic reviews and meta-analyses.Results We included 20 randomised controlled trial with a total of 1360 participants. Moderate effect sizes were found for increasing positive outcomes (g=−0.72, 95% CI: −1.31 to −0.14, k=10, numbers needed to treat (NNT)=2.55) and reducing negative outcomes (g=0.48, 95% CI: 0.18 to 0.78, k=8, NNT=3.76) when PPT was compared with waitlist control conditions at post-treatment assessment. When compared with active control conditions, PPT yielded large effect sizes for increasing positive outcomes (g=−0.92, 95% CI: −1.74 to −0.11, k=6, NNT=2.05) and reducing depression (g=0.94, 95% CI: 0.18 to 1.70, k=6, NNT=2.03) at post-treatment assessment. No significant differences in efficacy were found when compared with established treatments such as cognitive–behavioural therapy. Evidence was found to support an association between trial quality and effect sizes. For positive outcomes, higher trial quality was related to larger effect size. Whereas higher trial quality was associated with smaller effect size for depression. Follow-up assessments remained too scarce for most planned analyses.Conclusions Our findings support the short-term efficacy of PPT. However, results are to be regarded with due caution in the light of low number of trials. More high-quality trials that assess efficacy at follow-ups are needed to draw firmer conclusions on the long-term efficacy of PPT.PROSPERO registration number CRD42020173567.